Positive Solutions of Nonlocal Boundary Value Problem for High-Order Nonlinear Fractional -Difference Equations - Changlong Yu; Jufang Wang (Abstract and Applied Analysis)
We study the nonlinear -difference equations of fractional order , , , , , where is the fractional -derivative of the Riemann-Liouville type of order , , , , and . We obtain the existence and multiplicity results of positive solutions by using some fixed point theorems. Finally, we give examples to illustrate the results.